Pengaruh Aktivitas Fisik Senam Aerobik Low Impact terhadap Tekanan Darah pada Warga Kampung Bendung RT.04/RW.02 - Sri Nandini; Zia’ul Fatwa Andini Yusuf; Desty Endrawati Subroto; Nadia Fitriyati; Hernawati Hernawati (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Blood pressure is one of the non-communicable diseases that has become a global public health issue, as it often presents without symptoms but can lead to serious complications. Physical activities such as low-impact aerobic exercise have been proven to gradually and safely help reduce blood pressure, particularly in adults and the elderly. This study aims to determine the effect of low-impact aerobic exercise on blood pressure among residents of Kampung Bendung RT.04/RW.02, Bendung Subdistrict, Kasemen District, Serang City. The research used a quantitative approach with a pre-experimental design: one group pre-test and post-test. The study was conducted over five weeks with exercise sessions held once a week. The sample consisted of 20 women aged over 30 who participated regularly in the exercise sessions. Blood pressure measurements were taken before (pre-test) and after (post-test) the intervention using a digital sphygmomanometer. Data analysis using the Wilcoxon test showed a significant difference in blood pressure before and after the exercise, with a p-value of 0.000 (p < 0.05) for both systolic and diastolic pressure. The average systolic blood pressure decreased from 128.42 mmHg to 123.19 mmHg, and the diastolic pressure from 82.66 mmHg to 78.27 mmHg. It can be concluded that low-impact aerobic exercise is effective in lowering blood pressure and can be used as a preventive physical activity alternative for individuals at risk of hypertension.